Responsabilidade civil dos bancos no crime de saidinha bancária: análise legal e jurisprudencial - BACCIOTTI, Alair de Mendonça (2020)
With the advance of consumer relations and the growing number of crimes of "banking", it is necessary to establish the legal security of the subject, finding the most appropriate scenario for the legal operators, for banking institutions and users of the service provided. Article 14 of the Consumer Protection Code (CDC) establishes responsibilities of service providers. Banks are service providers. Among the services are cash withdrawals (cash, money) from customers, and it is necessary to find the causal link between this service provision and the bank crime, verifying the causal nexus theories and the jurisprudence on the subject in which the objective civil liability of these service providers is defined.